The life quality of adults with disabilities: psychological analysis of the subjective indicators - Khazova, Svetlana; Adeeva, Tatiana; Tikhonova, Inna; Shipova, Natalia (Social Welfare: Interdisciplinary Approach, 2017)
The article examines disabled-since-childhood adults’ quality of life. Study reveals conflict in empirical data: the respondents declare high level of one’s life quality but they do not have explicit goals in life and focus on seeking social support in difficult situations. Two groups of the respondents who differently assess their quality of life and control over their lives, have contrasting self-perception, and diverge in the existence of one’s life goals are compared.